1995
DOI: 10.1002/ddr.430340106
|View full text |Cite
|
Sign up to set email alerts
|

EP1 receptor antagonist blocks the diarrheagenic, but not cytoprotective, actions of a synthetic prostaglandin

Abstract: ~~ ~~Strategy, Management dnd Health P d~y orrnu ation ABSTRACTNaturally occurring and synthetic prostaglandins acting at EP type receptors have a number of physiological actions, including cytoprotective and antisecretory effects, that are therapeutically useful. In addition they can produce other effects, such as diarrhea. It is possible that these actions are mediated by different EP receptor subtypes. The actions of a subtype-selective prostaglandin agonist has suggested that diarrhea i s not due to activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Low levels of EP 1 mRNA expression in stomach, adrenal, and brain may not reflect a lack of a functional significance in these tissues. EP 1 receptor expression may be limited to discrete but physiologically critical regions, including hypothalamus (14) and gastrointestinal muscularis mucosa (48) where EP 1 may play roles in fever and intestinal motility, respectively (15,49).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Low levels of EP 1 mRNA expression in stomach, adrenal, and brain may not reflect a lack of a functional significance in these tissues. EP 1 receptor expression may be limited to discrete but physiologically critical regions, including hypothalamus (14) and gastrointestinal muscularis mucosa (48) where EP 1 may play roles in fever and intestinal motility, respectively (15,49).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, at these concentrations, neither receptor antagonist acted as an agonist in rabbit collecting duct, producing no change in baseline [Ca ϩϩ ] i , or 22 Na ϩ flux. While these compounds show reasonable in vitro activity, their in vivo utility is limited by this low potency, low water solubility, and avid binding to plasma proteins (11,15). Thus, characterization of the in vivo effects of EP 1 antagonists on Na ϩ balance awaits the availability of improved EP 1 receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies which were aimed to identify key structural requirements to synthesize EP selective agonists and/or antagonists and to provide insights to the mechanism of receptor ligand selectivity revealed that sensitive positions for agonist-activity at the EP1 receptor is the hydroxyl group at the carbon 15 position and C-1 carboxylate [29]. The selective EP1 antagonists may aid in characterization of the effects mediated by this receptor subtype [30][31][32]. The reported selective EP1 receptor antagonists are the acylhydrazide derivative SC51322 (by Searle group) [31], ZD6416 (by AstraZeneca) [33,34], ONO-8713 (by Ono) [35] and thiophene derivative ((by Merck Frosst) [36].…”
Section: Introductionmentioning
confidence: 99%